Palaeoproterozoic tectonic evolution of the Alto Tererê Group, southernmost Amazonian Craton, based on field mapping, zircon dating and rock geochemistry. (January 2016) - Lacerda Filho, J.V.; Fuck, R.A.; Ruiz, A.S.; Dantas, E.L.; Scandolara, J.E.; Rodrigues, J.B.; Nascimento, N.D.C.
Abstract: New geochemical and geochronological U–Pb and Sm–Nd data from amphibolites of the Alto Tererê Group, which are of Palaeoproterozoic age, are presented. The amphibolites are exposed in the central-eastern portion of the Rio Apa Block, southern Amazonian Craton, Mato Grosso do Sul, Brazil, and are composed of hornblende, plagioclase, quartz, biotite, cummingtonite and epidote. The amphibolites are subdivided into three lithofacies: (i) thinly banded amphibolites (metabasalts), (ii) coarse- and medium-grained amphibolites with relic subophitic texture (metagabbros), and (iii) amphibolites with relic cumulate texture (metapyroxenites). Chemical data also suggest the subdivision of the amphibolites into three different types. These rocks yield a U–Pb zircon age of 1768 ± 6 Ma and are therefore older than rocks of part of the Rio Apa Complex. Their Sm–Nd model ages range between 2.89 and 1.88 Ga, and their εNd (T) values range between −3.40 and + 3.74. Chemical analyses of these rocks indicate SiO2 concentrations between 45.23 and 50.65 wt.%, MgO concentrations between 4.34 and 8.01 wt.%, TiO2 concentrations between 0.91 and 1.74 wt.%, weakly fractionated rare-earth element (REE) patterns with mild depletion in heavy REEs, enrichment in large-ion lithophile elements (LILEs) and high-field-strength element (HFSEs), negative Nb, Ta and Co anomalies, positive Ba and Pb anomalies, low Ce concentrations, high Rb/Y ratios and low Th/La and Hf/Sm ratios. These features reflect metasomatism of the mantle wedge produced by sediments from the subducted plate. Various degrees of melting mark the evolution of the parent basic magmas, although subordinate crustal contamination may also have occurred. The geochemical signature of the amphibolites corresponds to that of tholeiitic basalts generated in an extensional back-arc-basin environment. The deposition in the basin apparently ceased during the first episode of compression and deformation at approximately 1.68 Ga, and the main deformation was most likely related to the San Ignácio Orogeny, which dates to approximately 1.3 Ga. Graphical abstract: Highlights: The Alto Tererê Group is a Paleoproterozoic metavolcanossedimentar sequence. It consists of amphibolite, garnet schist and quartzite of middle amphibolite facies. The unit consists of back arc basin rocks of the Amoguijá Arc. The earliest deformation in 1630 Ma developed in high degree, amphibolite facies. The second tectonic event (1.3 Ga), was in facies greenschist with vergence to W.